βTrCP facilitates MRN complex localization on chromatin to enhance DNA repair - Alejandro Belmonte-Fernández; Joaquín Herrero-Ruíz; Carmen Sáez; Miguel Á. Japón; Mar Mora-Santos; Francisco Romero (Communications Biology)
Abstract Genomic instability underlies various diseases, including cancer. This instability arises from defects in critical cellular processes, particularly those involved in DNA damage repair. Therefore, a detailed understanding of these repair mechanisms is essential for developing strategies to prevent or diagnose such diseases. The MRN complex, composed of MRE11, NBS1, and RAD50, is among the earliest elements involved in detecting DNA damage. Upon detecting DNA breaks, this complex triggers a cascade of signaling events that regulate both cell cycle arrest and DNA repair. These signaling pathways are tightly controlled by various post-translational modifications, notably ubiquitination. Although several ubiquitin ligases have been implicated in different stages of the DNA damage response, our knowledge remains limited. In this study, we reveal that βTrCP, a substrate-recognizing subunit of the SCF (SKP1/CUL1/F-box protein) ubiquitin ligase, interacts in vivo with the proteins of the MRN complex. These interactions occur in normally proliferating cells and are dependent on the GSK3 kinase. Moreover, we show that βTrCP enhances the recruitment of the MRN complex to chromatin through MRE11, thereby promoting the efficient DNA damage repair. Hence, alterations in βTrCP function affecting MRN dynamics could have severe consequences for the cell homeostasis.